Integrated management of genotype, row spacing and fertiliser application can lead to sustainable sugarcane production in the Indo-Gangetic Plains of India - Navnit, K; Lalita, R; Sumit, S; Sunil, K (Plant Science Today, 2026)
A poor nutrient management strategy leads to an imbalance in the soil nutrient status, which could have a long-term negative influence on crop output. Keeping this in view, a field experiment was conducted at Sugarcane Research Institute, Dr. Rajendra Prasad Central Agriculture University, Pusa, Samastipur Bihar, to assess performance of early maturing sugarcane genotypes with two row configurations (90 and 120 cm) under two levels of macronutrients (NPK) i.e. N150 + P37.1 + K49.8 and N187.5 + P46.4 + K62.3 kg/ha on soil nutrient equilibrium sugarcane crop during 2018–19. Genotype CoP 13437 recorded a significantly higher tiller population and number of millable canes (169.7 and 114.9 × 103/ha) while genotype CoSe 95422 showed the highest B:C ratio (2.33). Maximum cane yield was observed in 90 cm row spacing with the increased NPK level and the increase in cane yield under N187.5 + P46.4 + K62.3 kg/ha was to the tune of 27.5 %. Genotype CoSe 95422 produces a higher cane yield (102.6 t/ha) of sugarcane, followed by CoP 13437 (101.5 t/ha). The uptake of macronutrients increased when more fertiliser was applied (280, 27.3 and 318.2 NPK kg/ha). With increasing fertility levels (N187.5 + P46.4 + K62.3 kg/ha), a net gain of NPK was observed. Therefore, balanced nutrient management combined with appropriate genotype selection and row spacing significantly enhanced sugarcane productivity and improved soil nutrient status for sustainable cultivation.